2006
DOI: 10.1007/s00726-006-0399-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 28 days of beta-alanine and creatine monohydrate supplementation on aerobic power, ventilatory and lactate thresholds, and time to exhaustion

Abstract: The effect of beta-alanine (beta-Ala) alone or in combination with creatine monohydrate (Cr) on aerobic exercise performance is unknown. The purpose of this study was to examine the effects of 4 weeks of beta-Ala and Cr supplementation on indices of endurance performance. Fifty-five men (24.5 +/- 5.3 yrs) participated in a double-blind, placebo-controlled study and randomly assigned to one of 4 groups; placebo (PL, n = 13), creatine (Cr, n = 12), beta-alanine (beta-Ala, n = 14), or beta-alanine plus creatine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
4
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 20 publications
7
93
4
2
Order By: Relevance
“…We also did not find any relationship 22 between the magnitude of increase in muscle carnosine concentration and the change in time--trial 23 performance. To our knowledge, this study is the first to document the lack of effect of beta--24 supplementation on an actual endurance exercise performance test as previous studies utilised 1 incremental exercise tests (Stout et al, 2007;Zoeller et al, 2007) and high--intensity efforts at the 2 end of a prolonged cycling protocol (Van Thienen et al, 2009). 3 A key finding in this study is the largest ever--reported relative increase in muscle carnosine 4 concentration following beta--alanine supplementation.…”
Section: Discussion 18mentioning
confidence: 53%
“…We also did not find any relationship 22 between the magnitude of increase in muscle carnosine concentration and the change in time--trial 23 performance. To our knowledge, this study is the first to document the lack of effect of beta--24 supplementation on an actual endurance exercise performance test as previous studies utilised 1 incremental exercise tests (Stout et al, 2007;Zoeller et al, 2007) and high--intensity efforts at the 2 end of a prolonged cycling protocol (Van Thienen et al, 2009). 3 A key finding in this study is the largest ever--reported relative increase in muscle carnosine 4 concentration following beta--alanine supplementation.…”
Section: Discussion 18mentioning
confidence: 53%
“…It is important to emphasize that most investigations involving BA supplementation have enrolled physically active individuals, rather than well-trained athletes (Hill et al 2007;Stout et al 2007;Zoeller et al 2007;Smith et al 2009). Despite the methodologic constraints inherent in studies involving athletes (e.g., reduced sample size, competition schedule constraints, inability to perform invasive assessments), they are important to substantiate the efficacy of nutritional aids in sports.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exercise performance improvement by L-ornithine hydrochloride ingestion may not be expected in the case of the present relatively brief, high-intensity exercise. Many previous studies have reported the effects of amino acid ingestion on improving performance, but a variety of exercise types were used (de Araujo et al, 2006;Norton and Layman, 2006;Zoeller et al, 2007;Smith et al, 2008). Namely, there are studies which used short duration, high-intensity exercise and studies which used long term, moderate-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%